ANALISIS KEBUTUHAN DAN PENGEMBANGAN MODEL SEKOLAH KESETARAAN DI PROVINSI KEPULAUAN BANGKA BELITUNG - Asyraf Suryadin; Maulina Hendrik; Yuanita; Dzihan Khilmi Ayu Firdaus; Rusdi; Mardani (UNMUHBABEL Press, 2024)
This study aims to gather preliminary information on the design of the high school equivalency model before formulating the particular determination on the high school equivalency model developed by Community Learning Center. The technique of collecting data used observation, interview, questionnaire, and documentation, and analyzed using descriptive qualitative. The results are showed that the implementation of school equivalency consists of learning program equivalent A, learning program equivalent B, and learning program equivalent C. The reasons why subjects took the School equivalency because 1) social status need, 2) schools’ Dropout rates, 3) educational facilities, 4) organization apparatus needs, 5) low motivation, 6) child marriage. Based on the deep analysis, the school equivalency program is not optimal; there is neither innovation in the management learning process nor implementation in the teaching process; there is a lack of professional tutors; there is difficulty in arranging the time of study because of the learners' background. The findings propose the development of the high school equivalency model based on entrepreneurship. The model intends the learners to study everywhere and every time; creates the learners’ profession as a value as well gives the learners courses based on the ability through the cooperative activities.